2004
DOI: 10.1111/j.1471-4159.2004.02564.x
|View full text |Cite
|
Sign up to set email alerts
|

NFATc1 activates the acetylcholinesterase promoter in rat muscle

Abstract: Nuclear factor of activated T-cells (NFAT) plays a role in the response of muscle to chronic contractile activity that can result in fiber type switching and hypertrophy. These effects are due in part to activation of target genes following Ca 2+ -mediated nuclear translocation of NFAT. Acetylcholinesterase (AChE), a component of the neuromuscular junction, is regulated by chronic muscle and nerve activity through changes in intracellular Ca 2+, suggesting that the Ache gene may be a potential downstream targe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 45 publications
(97 reference statements)
1
8
0
Order By: Relevance
“…Mouse AChE promoter region contains three consensus binding sites for NFAT: one of them is conserved in mouse, rat, and human. However, the constitutively active NFATc1, instead of inhibiting, moderately stimulated the activity of the AChE gene promoter in primary rat muscle culture (Cohen and Randall, 2004). Conversely, in line with our results in adult muscles, CsA-induced inhibition of calcineurin increased the levels of AChE mRNA in cultured C2C12 myotubes, but this was primarily attributable to increased AChE mRNA stability and not to enhanced transcription (Luo et al, 1999).…”
Section: Calcineurin Signaling Pathway and Muscle Ache Regulationsupporting
confidence: 80%
“…Mouse AChE promoter region contains three consensus binding sites for NFAT: one of them is conserved in mouse, rat, and human. However, the constitutively active NFATc1, instead of inhibiting, moderately stimulated the activity of the AChE gene promoter in primary rat muscle culture (Cohen and Randall, 2004). Conversely, in line with our results in adult muscles, CsA-induced inhibition of calcineurin increased the levels of AChE mRNA in cultured C2C12 myotubes, but this was primarily attributable to increased AChE mRNA stability and not to enhanced transcription (Luo et al, 1999).…”
Section: Calcineurin Signaling Pathway and Muscle Ache Regulationsupporting
confidence: 80%
“…RCAN1.4 and BNP transcripts were analyzed as readouts, as they are direct targets of NFAT (8,43,51), and both are activated in hypertrophy (22,26). We report that increases in RCAN1.4 and BNP levels are amplified in isoproterenol-treated FHL2 Ϫ/Ϫ mice.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that the AChE promoter contains AP-1, AP-2, GRE, binding sites (Getman et al, 1995;Perry et al, 2002;Cohen and Randall, 2004;Meshorer et al, 2004;Meshorer et al, 2005). c-Jun and c-fos can form AP-1 transcription factor.…”
Section: Discussionmentioning
confidence: 99%